2020
DOI: 10.3390/agriculture10110574
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Phytochemical Responses of Spinach Baby Leaves Grown in a PFAL System with LEDs and Saline Nutrient Solution

Abstract: Spinach is a leafy vegetable containing a plethora of bioactive compounds. Our study aimed to evaluate the physiological (i.e., JIP-test) and phytochemical response of spinach baby leaves grown with regular or mildly saline (40 mM NaCl) nutrient solution and irradiated by four light-emitting diodes (LEDs) with broad spectra. T1 (highest red and far-red, low blue) and T3 (high red, balanced blue, green and far-red) led to a better developed photosynthetic apparatus compared to T2 (red peak in 631 nm) and T4 (hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
2
9
0
1
Order By: Relevance
“…Finally, there was no interaction between light and salinity for yield (Table 1), in agreement with the results of Bantis et al [34], who did not detect yield differences in spinach baby leaf among mildly saline (40 mM NaCl) and non-saline treatments for the different LEDs tested.…”
Section: Yieldsupporting
confidence: 91%
“…Finally, there was no interaction between light and salinity for yield (Table 1), in agreement with the results of Bantis et al [34], who did not detect yield differences in spinach baby leaf among mildly saline (40 mM NaCl) and non-saline treatments for the different LEDs tested.…”
Section: Yieldsupporting
confidence: 91%
“…By determining the total soluble solids of microgreens, it is possible to quantify the tastiness of these commodities, an important aspect for consumers. In a study with spinach (Spinacia oleracea), baby leaves grown under broad-spectrum LEDs did not exhibit significant differences in soluble sugar content [34]. However, lettuce (Lactuca sativa) treated with white-red light produced greater amounts of sugars compared to white-blue light [35].…”
Section: Total Soluble Solidsmentioning
confidence: 96%
“…These authors showed that antioxidant capacity and phenolic accumulation were improved under blue LEDs. Moreover, Bantis et al [76] used different LED lamps that combined UV, blue, green, red, and far-red at different percentages. Under 150 µmol m −2 s −1 of the treatment with a high percent of red (67%) and far-red (23%) the yield production was significantly increased.…”
Section: Preharvest Uv and Visible Spectrum Illumination Strategies T...mentioning
confidence: 99%